YORUBA TRADITIONAL INSTITUTION AND MAINTENANCE OF LAWS AND ORDERS IN THE PRE-COLONIAL PERIOD - O. E., BABALOLA (PEOPLE: International Journal of Social Sciences, 2017)
Traditional institution was the most relevant institution in all the Yoruba towns and villages in the pre- colonial period. It represented the central point of the people’s cultural, social, economic, political and spiritual engagement. Traditional Yoruba rulers were the trustees of the various communities and also responsible for the general well- being of their people. For most of these functions to be achieved, there was the need for laws and orders to guide the action and day to day life of the people. The paper therefore sets to look at the roles played by the Yoruba traditional institution in the maintenance of these laws and orders. The paper articulates the structure of Yoruba traditional institution, the sources of their laws and the instruments used in the maintenance of the laws and orders. Historical analysis approach is explored in writing this paper.